Nuclear Intron Sequence Variation of the Bulinus globosus Complex (Mollusca: Planorbidae): Implications for Molecular Systematic Analyses - Chairat Tantrawatpan; Kotchaphon Vaisusuk; Chrysantus M. Tanga; Warayutt Pilap; Naruemon Bunchom; Ross H. Andrews; Tongjit Thanchomnang; Wanchai Maleewong; Weerachai Saijuntha (Biology)
Urinary schistosomiasis is caused by the blood fluke Schistosoma haematobium, which is predominantly found in Africa. The freshwater snail Bulinus globosus is its main intermediate host. The species that make up the B. globosus group are genetically complex, and their taxonomic status remains controversial. Genetic variation, heterozygosity, and DNA recombination in B. globosus were examined using the mitochondrial cytochrome c oxidase subunit 1 (COI) and the intron 3 region of the arginine kinase gene (AkInt3). A total of 81 B. globosus snails were collected from three different localities in Kwale County, Kenya. Genomic diversity, heterozygosity, DNA recombination, and haplotype network were calculated using AkInt3 sequences. Low polymorphism in the COI sequence divided B. globosus into six haplotypes (C1–C6). However, AkInt3 sequencing studies showed high polymorphisms, classifying 81 B. globosus snails into 44 haplotypes (H1–H44). These haplotypes were separated into three haplogroups (I–III). AkInt3 sequence heterozygosity was also found. DNA recombination haplotypes between haplogroups were commonly found in heterozygous samples. AkInt3 sequence studies showed high levels of genetic polymorphism and heterozygosity, supporting its use as a genetic marker for elucidating the population genetics of B. globosus. Furthermore, our study showed that B. globosus populations in Kenya form a “species complex”.